2015
DOI: 10.1038/srep14925
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between microRNA expression and classical risk factors in the risk of coronary heart disease

Abstract: The aim of this study was to identify the synergistic effect of microRNA expression with classical risk factors of coronary heart disease (CHD) and to explore their diagnostic value for coronary stenotic lesions in subjects with CHD. Plasma samples were obtained from 66 subjects with CHD and from 58 control individuals. A quantitative reverse-transcription PCR (RT-qPCR) assay was conducted to confirm the relative expressions of the known CHD-related miRNAs. The severity of coronary atherosclerosis was based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 63 publications
0
26
0
5
Order By: Relevance
“…Non-coding RNA-based approaches provide new opportunities to develop novel biomarkers. Small RNAs such as microRNAs (miRNAs) have been proposed as sensitive and specific biomarkers of cardiovascular disease2425. Extracellular lncRNAs are potent biomarkers in cancer26.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNA-based approaches provide new opportunities to develop novel biomarkers. Small RNAs such as microRNAs (miRNAs) have been proposed as sensitive and specific biomarkers of cardiovascular disease2425. Extracellular lncRNAs are potent biomarkers in cancer26.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies [28], nine CHD-related miRNAs were proposed as candidates in the study. This includedmiR-122, miR-133b [29], miR-214 [30], miR-21, miR-106a [31], miR-130a, miR-155, miR-221 [32], and miR-125b [33-36].…”
Section: Subject and Methodsmentioning
confidence: 99%
“…Another interesting characteristic of disease-specific miRNAs is that they may be ethnicity specific [20]. Moreover, accumulating evidence indicates that some miRNAs may be specific for patients with CHD [21]. However, the potential role of these miRNAs in multi-ethnic CHD patients has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, just as we found that postnatal exposure to a Western diet unmasked metabolic defects in obese-born mice, 13 so does the dietary challenge unmask changes to the cardiac miRNA pool of obese-born offspring. Whereas these changes were subtle, the downregulation of miR-125, a miRNA implicated in cardiac fibrosis, 14 coronary heart disease risk, 15 and known for its myocardial protective effects in reperfusion injury, was notable. 16 The most significant expression change in response to maternal obesity, upregulation of miR-148-3p, was associated with several cardiac disease pathways as well as ErbB signaling, a pathway critical for both cardiac development and adult heart function.…”
Section: Discussionmentioning
confidence: 99%